Penerapan E-Learning Berbasis Moodle Menggunakan Metode Problem Based Learning di SMK Negeri 1 Pasuruan - Teguh Arifianto (SMATIKA JURNAL : STIKI Informatika Jurnal, 2017)
The learning process used in the X class of Computer Engineering and Computer Networking Competition classes still use teacher centered method, where teachers are more dominant than the students in the learning process. Thus, students who do not have the motivation to learn or not pay attention to the process of learning instead of opening an online game for the browser or active with social media.This study aims to apply e-learning based on moodle Problem Based Learning method in SMK Negeri 1 Pasuruan. The subjects of this study are students of class X TKJ 1 SMK Negeri 1 Pasuruan, amounting to 36 people. To know the teacher and student response to the implementation of moodle based e-learning mnggunakan problem based learning method obtained by using questionnaire method / questionnaire. Based on the results of the research, the conclusion that can be taken is the application of moodle based e-learning using problem based learning method on the subjects of Computer Assembly class X TKJ 1 has been tested. From the results of questionnaire data analysis given to the teacher respondents obtained an average percentage score of 81.87% and student respondents got an average percentage score of 88.86%. This shows that the application of moodle based e-learning using problem based learning method in SMK Negeri 1 Pasuruan is very effective and in terms of moodle performance using problem based learning method in its application can be quite good.